Физическая модель гранулированной токопроводящей среды - Захарченко, С.Н. (Технічна електродинаміка, 2012)
The electro-physical model of the granulated current-carrying medium at it spark-eroded processing is offered. Formulas for calculation of parameters of active and reactive elements of an equivalent circuit are resulted. Their dependences on electro-physical and geometrical characteristics of elements of model are analyzed. Frequency ranges in which some elements of an equivalent circuit can be neglected are defined.